Authenticity of engaging Student Addressed education stratagems in Psychology Course from the Teachers’ Perspective in Kuwait - Abed Al-Rahman Shamekh Ayed Snaitan Al-Ershaidy (مجلة العصر للعلوم الانسانية والاجتماع, 2023)
The present study aimed to explore the reality of employing student-centred learning strategies in psychology course from the teachers’ perspective in Kuwait. Those strategies are represented in the problem-based and project-based strategies. The researcher selected a purposive sample that consists from 40 female and male teachers who teach psychology course. Those teachers were selected from 40 schools located in Al-Farwaniyah, Kuwait. Questionnaire forms were distributed to those teachers. All the forms were retrieved and deemed valid for analysis. SPSS software was employed for having the data analysed. It was found that the extent of employing the student-centred learning strategies (i.e. problem-based and project-based strategies) in psychology course from the teachers’ perspective in Kuwait in high. The researcher recommends conducting studies about the effectiveness of employing student-centred learning strategies in other courses in Kuwait.